2004
DOI: 10.1542/peds.113.6.e530
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Evening Admissions and Higher Mortality Rates in the Pediatric Intensive Care Unit

Abstract: ABSTRACT. Background. Previous research investigating the relationship between the time of admission and mortality rates has yielded inconsistent results and has not been conducted in the pediatric intensive care unit (PICU) patient population.Objective. To determine whether an association between the time of admission (weekday versus weekend and daytime versus evening) and the risk of death exists among pediatric patients included in a cohort of children admitted to a national sample of PICUs.Design/Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
73
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 33 publications
8
73
1
4
Order By: Relevance
“…While they found that the overall adjusted mortality rate was not different for patients admitted to the ICU on weekends when compared with weekdays (considering the ICUs as a whole), they did observe a significant weekend effect for patients admitted to the surgical ICU. Weekend versus weekday mortality rates have also been examined with respect to pediatric ICUs, 3,16 while other studies have found the absence of the weekend effect in ICUs when there is an intensivist in-house full-time (24 hours a day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While they found that the overall adjusted mortality rate was not different for patients admitted to the ICU on weekends when compared with weekdays (considering the ICUs as a whole), they did observe a significant weekend effect for patients admitted to the surgical ICU. Weekend versus weekday mortality rates have also been examined with respect to pediatric ICUs, 3,16 while other studies have found the absence of the weekend effect in ICUs when there is an intensivist in-house full-time (24 hours a day).…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8]11,[13][14][15][16]23,29,31,34 These databases could potentially include coding errors, usually originating from the hospital level, 9 although it seems likely that such errors would be consistent across the entire database rather than isolated to the weekend admissions. In addition, the database contains discharge records, which include discharges to other hospitals.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][11][12][13][14][15][16]19,20,[23][24][25] The "weekend effect" on pediatric neurosurgical procedures is unknown. Therefore, our primary aim was to abbreviation ASA = American Society of Anesthesiologists.…”
mentioning
confidence: 99%
“…Th e Centers for Medicare & Medicaid Services evaluated ICU readmissions as a candidate ICU quality indicator 1 based on evidence that readmissions are associated with increased mortality and cost [2][3][4][5][6][7][8][9][10][11][12] and because they are presumed to result from "premature" ICU discharge, 13 bed shortages, 14,15 or poorly orchestrated handoff s. 10,16 However, other reports show that while patients discharged when ICUs are more strained have increased odds of ICU readmission, the risk of death is no higher, suggesting that decisions preceding ICU readmissions may not cause the excess mortality with which they are associated. [17][18][19] Additionally, the performance of ICUs on ICU readmissions is not correlated with performance on other measures of ICU quality, such as mortality or process measures.…”
mentioning
confidence: 99%